2018
DOI: 10.3897/neobiota.41.26599
|View full text |Cite
|
Sign up to set email alerts
|

Global environmental and socio-economic impacts of selected alien grasses as a basis for ranking threats to South Africa

Abstract: Citation: Nkuna KV, Visser V, Wilson JRU, Kumschick S (2018) Global environmental and socio-economic impacts of selected alien grasses as a basis for ranking threats to South Africa. NeoBiota 41: 19-65. https://doi. AbstractDecisions to allocate management resources should be underpinned by estimates of the impacts of biological invasions that are comparable across species and locations. For the same reason, it is important to assess what type of impacts are likely to occur where, and if such patterns can be g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The Environmental Impact Classification for Alien Taxa has been applied to various taxa that are known to occur as alien species in South Africa including grasses (Visser et al 2017;Nkuna et al 2018;Canavan et al 2019), amphibians (Kumschick et al 2017), birds (Evans et al 2016), mammals (Hagen and Kumschick 2018), fish (Marr et al 2017), gastropods (Kesner and Kumschick 2018), and some other invertebrates (Nelufule 2018). Most EICAT assessments performed to date have been done at a global scale, i.e.…”
Section: Impact-scoring Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Environmental Impact Classification for Alien Taxa has been applied to various taxa that are known to occur as alien species in South Africa including grasses (Visser et al 2017;Nkuna et al 2018;Canavan et al 2019), amphibians (Kumschick et al 2017), birds (Evans et al 2016), mammals (Hagen and Kumschick 2018), fish (Marr et al 2017), gastropods (Kesner and Kumschick 2018), and some other invertebrates (Nelufule 2018). Most EICAT assessments performed to date have been done at a global scale, i.e.…”
Section: Impact-scoring Schemesmentioning
confidence: 99%
“…There are six grass species that have had EICAT assessments done at a national scale for South Africa, with Arundo donax (Giant Reed) and Glyceria maxima (Reed Meadow Grass) evaluated as having major impacts (Visser et al 2017;Nkuna et al 2018;VK Nkuna, unpublished data). These two species have been implicated in competitively displacing native species; A. donax, for example, dominates riparian areas and can locally exclude native plants (Holmes et al 2005;Guthrie 2007), while G. maxima has locally displaced some native wetland species (Mugwedi 2012).…”
Section: Grassesmentioning
confidence: 99%
“…This does not, however, mean that the impacts should not be recorded nor that they will require management to reduce negative impacts (e.g. see Nkuna et al 2018 Only taxa marked X clearly fulfilled criteria for listing as "invasive" (sensu Richardson et al 2000b) in natural or semi-natural ecosystems; those marked with W are listed as "invasive" in other regions by Weber (2017), but do not meet all criteria for listing as invasive sensu Richardson et al (2000b)…”
Section: Naturalised Distributions and Invasive Status As Different Dmentioning
confidence: 99%
“…Nkuna, et al [58] analysed environmental and socio-economic impacts of 58 selected alien grass species in South Africa by applying the Generic Impact Scoring System method. They found that these species caused a wide range of negative impacts across most habitats.…”
Section: Invasivenessmentioning
confidence: 99%